Linking therapeutic (is)landscapes, experiences of digitality and the quest for wellbeing - Erin James; Robin Kearns (Wellbeing, Space and Society, 2020)
In this paper we examine experiences associated with tourism on Turtle Island, an exclusive privately-owned island resort in Fiji. Tropical islands have long been marketed as ‘getaways’ and places where tourists seek wellbeing. Our study considers the affective experiences and recollections of visitors as well as the views of workers at such resorts. Through mobilising the therapeutic (is)landscape idea and the concept of digitality, we advocate an extension to understandings of wellbeing into ‘well-becoming’. In this study, well-becoming occurs as a dynamic process of journeying across bluespace in search of wellness. From participatory fieldwork, online surveys, the digital record and interviews, we note that guests paradoxically seek privacy yet also transmit their wellbeing experiences to the world beyond through social media. Upon departure, they maintain affective bonds with place through social media. We show that staff also lean on social media to ‘keep in touch’ when necessarily at-a-distance from families. We identify tensions between the quest for ‘escape’ to such places and the quest for wellbeing within the gaze of digital media. We conclude that despite the disciplining influence of the ‘inverted gaze’ of digital power, visitors nonetheless experience restorative effects within this island setting.